Exploring electric vehicle participation in the Icelandic balancing market as Virtual Power Plant - Fritz Steingrube 1992- (2017)
The electrification of transport sector has been named as one of the key measures to mitigate the global CO2 emissions. Due to the local energy mix, Iceland has a lot of potential to effectively reduce CO2 emissions by further increasing the share of electric vehicles (EV) in their fleet. To incentivize the increased rollout, finan-cial incentives for individual car owners need to be created. The idea is to capital-ize on the fact that small vehicles are rarely moving more than 30 minutes per day. Through vehicle-to-grid (V2G) technology, the storage capacities of the EVs could be on the Icelandic balancing market for balancing when the vehicles are not in use. This research sets out to determine if it is possible for a fleet of EVs to be able to compete in the Icelandic balancing market. In order to compete, the vehicles have to be pooled and managed as single acting entity through an aggregator. All vehi-cles pooled by the aggregator are acting as a Virtual Power Plant (VPP). To determine the viability of the idea, this research ran an agent based simulation, modelling the mobility behavior and balancing market using Icelandic data. The results show that a VPP of EV batteries can in fact participate successfully in the balancing market. Both participating vehicle owners and the VPP operator can ac-cumulate profits – to what extent is however highly dependent on inter alia bat-tery costs, the electricity retail price, and the minimum bid size for participation in the balancing market. Rafvæðing farartækja er sögð ein af lykilaðgerðum til þess að draga úr hnattrænum útblæstri CO2. Á Íslandi er raforka framleidd með lágu hlutfalli af CO2 sem bíður uppá óvenju mikla möguleika í minnkun á útblæstri CO2 samhliða því að auka hlutfall rafknúinna farartækja (RF). Til að hvetja til aukinnar notkunar þarf að búa til fjárhagslega hvata fyrir einstaklinga. Hugmyndin er að nýta sér þá staðreynd að lítil farartæki eru sjaldan á ferð lengur enn 30 mínútur á dag. Með tækni sem tengir RF við dreifikerfi er hægt að nýta ...